Tau’s Three-Repeat Domain and EFhd2 Co-incubation Leads to Increased Thioflavin Signal - Vega, Irving E.; Sutter, Alexandra; Parks, Luke; Umstead, Andrew; Ivanova, Magdalena I. (Frontiers in Neuroscience, 2018)
Aggregation of the protein tau is a pathological hallmark of Alzheimer’s disease (AD) and related disorders. However, the molecular mechanisms that lead to tau protein aggregation are still unclear. Previously, we showed that EFhd2 protein is associated with pathological aggregated forms of tau in AD brain. Further, immuno-gold analyses of purified tau aggregates showed that EFhd2 co-localized with filamentous tau structures. We demonstrated that EFhd2’s coiled-coil domain is required for its association with tau proteins. However, it is unknown the role that EFhd2 plays in tau aggregation. Here, we show that incubation of K19-tau with substoichiometric amount of EFhd2 promote the formation of amyloid structures in vitro. The result suggests that EFhd2 may play a role in the biogenesis of aggregated tau.